Sex Hormones and Aging Modulate Interferon Lambda 1 Production and Signaling by Human Uterine Epithelial Cells and Fibroblasts - Patel, Mickey V.; Hopkins, Daniel C.; Barr, Fiona D.; Wira, Charles R. (Frontiers in Immunology, 2021)
Estradiol (E2) and progesterone (P) have potent effects on immune function in the human uterine endometrium which is essential for creating an environment conducive for successful reproduction. Type III/lambda (λ) interferons (IFN) are implicated in immune defense of the placenta against viral pathogens, which occurs against the backdrop of high E2 and P levels. However, the effect of E2 and P in modulating the expression and function of IFNλ1 in the non-pregnant human uterine endometrium is unknown. We generated purified in vitro cultures of human uterine epithelial cells and stromal fibroblast cells recovered from hysterectomy specimens. Poly (I:C), a viral dsRNA mimic, potently increased secretion of IFNλ1 by both epithelial cells and fibroblasts. The secretion of IFNλ1 by epithelial cells significantly increased with increasing age following poly (I:C) stimulation. Stimulation of either cell type with E2 (5x10-8M) or P (1x10-7M) had no effect on expression or secretion of IFNλ1 either alone or in the presence of poly (I:C). E2 suppressed the IFNλ1-induced upregulation of the antiviral IFN-stimulated genes (ISGs) MxA, OAS2 and ISG15 in epithelial cells, but not fibroblasts. Estrogen receptor alpha (ERα) blockade using Raloxifene indicated that E2 mediated its inhibitory effects on ISG expression via ERα. In contrast to E2, P potentiated the upregulation of ISG15 in response to IFNλ1 but had no effect on MxA and OAS2 in epithelial cells. Our results demonstrate that the effects of E2 and P on IFNλ1-induced ISGs are cell-type specific. E2-mediated suppression, and selective P-mediated stimulation, of IFNλ1-induced ISG expression in uterine epithelial cells suggest that the effects of IFNλ1 varies with menstrual cycle stage, pregnancy, and menopausal status. The suppressive effect of E2 could be a potential mechanism by which ascending pathogens from the lower reproductive tract can infect the pregnant and non-pregnant endometrium.